Erythrocyte factors concerned in the inhibition of ALA-D by lead. Issue 3 (August 1981) - Sakai, T; Yanagihara, S; Ushio, K
Abstract : Erythrocyte factors are concerned in the inhibition of delta-aminolaevulinic acid dehydratase (ALA-D) by lead at 20 to 100 nM concentrations. The activity of the factors in detected in Hb fractions from Sephadex G-200 gel filtration of erythrocyte supernatant. After gel filtration of erythrocyte supernatant from a lead worker, 50% of lead is found in ALA-D fractions, although the fractions recover from ALA-D inhibition. The recovered activity is reinhibited if the enzyme fraction is preincubated with Hb fraction obtained from the same chromatography. Similarly obtained enzyme from a normal subject is also inhibited when it is preincubated with normal Hb fraction and lead acetate at 20 to 100 nM concentrations. The extent of the inhibition depends on the concentrations of Hb fraction and lead acetate preincubated. Reinhibition of lead worker enzyme with normal Hb fraction may be deleted not only by heating but also by zinc or DTT as well. Hb fraction heated at 60 degrees C for 5 min is also able to induce the lead-inhibition of the activity in ALA-D fraction. Half life of the factors is 26 min at 60 degrees C and 3 min at 80 degrees C.